Aerobic Oxysulfonylation of Alkenes Leading to Secondary and Tertiary β‐Hydroxysulfones1. Issue 28 (23rd May 2013) - Lu, Qingquan; Zhang, Jian; Wei, Fuliang; Qi, Yue; Wang, Huamin; Liu, Zhiliang; Lei, Aiwen
<x xml:space="preserve">Abstract</x> New channel! A novel and attractive dioxygen activation by sulfinic acids was explored that is capable of performing efficiently without the assistance of transition metals or radical initiators. This reaction furnishes secondary and tertiary β‐hydroxysulfones under mild conditions; β‐hydroperoxysulfone was isolated as an important intermediate.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>